A Metaphoric Nexus of Terms in Neuroanatomy - Petrosyan, Alina (Armenian Folia Anglistika, 2015)
This article offers an overview on the usage of technological metaphors in medicine, and in Neuroanatomy in particular. Exploring major technological metaphors surrounding human brain and nervous system, the paper aims at illustrating the cognitive functions these metaphors have in communicating clinical phenomena and pathologies. The neuroanatomical section in the “Gray’s Anatomy” – the clinical Bible of medicine – has served a major reference point for the analysis of metaphors.